2014
DOI: 10.5293/ijfms.2014.7.2.068
|View full text |Cite
|
Sign up to set email alerts
|

Design and Simulation of Very Low Head Axial Hydraulic Turbine with Variation of Swirl Velocity Criterion

Abstract: The type of turbine developed is based on the very low head of water potential source for the electric power production. The area of research is focused for the axial water turbine that can be applied at the simple site open channel with has a very low cost and environmental impact compared to the conventional hydro installation. High efficiency of axial turbine which applied to the very low potential head will made this type of turbine can be used at wider potential site. Existing irrigation weir and river ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The turbine runner was designed on the basis of free-vortex theory combined with Euler's head equation; the design process of the turbine runner was presented in detail in previous research performed by Tran et al [18]. The well-known free-vortex theory originally comes from the law of conservation of angular momentum that was applied in designing several types of compressible and incompressible flow machinery [19,20]. The current surveyed turbine was developed to operate with a gross head of 2 m, a rated flow of 0.25 m 3 /s, and a rotational speed of 450 rpm.…”
Section: Physical Model Of Propeller Turbinementioning
confidence: 99%
“…The turbine runner was designed on the basis of free-vortex theory combined with Euler's head equation; the design process of the turbine runner was presented in detail in previous research performed by Tran et al [18]. The well-known free-vortex theory originally comes from the law of conservation of angular momentum that was applied in designing several types of compressible and incompressible flow machinery [19,20]. The current surveyed turbine was developed to operate with a gross head of 2 m, a rated flow of 0.25 m 3 /s, and a rotational speed of 450 rpm.…”
Section: Physical Model Of Propeller Turbinementioning
confidence: 99%
“…This type is the very low head single rotor turbine or VLHSRT. Although this turbine can work with high efficiency [1,2,3], the authors wishes to be able to improve and developing application of this turbine type in order to expand its use. For this reason, design of the very low head turbine is developed which using two rotors that rotating in opposite.…”
Section: Turbine Designmentioning
confidence: 99%
“…In lower loads, the blades are adjusted in a specific way to obtain best efficiency which needs supplementary adjustments of guide vanes stagger angel to create fully axial flow at the runner outlet [14]. Muis and Sutikno [15] considered swirl velocity, free vortex, and forced vortex to design the runner of a VLH turbine using Goettingen0480 airfoil. They applied kω-SST model to solve the 3D flow in the turbine, and their numerical results showed that the generated power for forced vortex criterion is 15% higher than the power produced by free vortex criterion.…”
Section: Introductionmentioning
confidence: 99%